Foreign Capital Inflows, Domestic Saving, and Economic Growth: The Case of Thailand - Saengthong, Prapaporn (2010)
Understanding the growth process is central to development economics. Analyzing and interpreting the determinants of growth, either the process has worked or failed in countries is ultimately an empirical issue. This study attempts to explain this issue looking not only at the economic impact of FCI and domestic savings on economic growth in Thailand but also on how these two components of financial capital are related in a dynamic framework. The model for analysis was developed base on the Two Gap economic growth model. The analysis of this relationship is based on quarterly time series data for the period of 1993-2007. To capture the dynamic relationship, the model was estimated for error correction both by single equation framework and also by Johansen's procedure. The results show that domestic savings, foreign capital inflows give a positive effect to Thailand's economic growth. The effect of domestic savings on growth is bigger than the effect of foreign capital inflows. The results of the study also show that domestic savings and foreign capital inflows has a significant negative relationship which is to say they are substitute. Other variables of interest in the study are human capital and interest rate. The analysis showed that, human capital and interest rate provide very useful results in explaining their contribution to Thailand's economic growth. The role of human capital is very crucial. Human capital is positively and significantly affects the growth. These findings seem to support the validity of the endogenous growth model for the economy. The interest rate seems to influence domestic savings significantly. This finding, particularly on human capital has some policy relevance at the macro development perspective. The economics shock from financial crisis for the period of 1997-1999 gave significant effects to domestic savings and foreign capital inflows. The results of analysis indicated that it has negative to domestic savings but positive effect to foreign capital inflows, this results also indicates a substitution between this two capitals.